Economic perspectives for effective control of diabetes mellitus type 2 with fixed combination of basal insulin analog and GLP-1 agonist - S. K. Zyryanov; I. N. Dyakov (Izdatelstvo OKI, 2019)
Fixed antidiabetic drugs' combinations have aim to improve Diabetes Mellitus type 2 (DMT2) control as well as a safety treatment increasing. Soliqua SoloStar® is a new registered drug for control fasting and prandial glucose levels, contained insulin glargine 100 Ul/ml and lixisenatide. In the published non-direct comparison, it was more effective for DMT2 control vs insulin glargine 100 Ul/ml and lixisenatide separately, and daily insulin dose was less on 22 UI.Aim. To evaluate of Soliqua SoloStar® reasonability for inclusion from pharmacoeconomics point of view into the State program of the free medical Aid guarantees.Materials and methods. Retrospective comparative economic analysis based on published data an new methodology treatment with Soliqua SoloStar® in compare with the current treatment methodology with usage of insulin glargine and lixisenatide separately. Common used methodology of clinical-economic analysis was used, and target group of patients was established based on Federal Diabetes Register. Direct medical cost was defined as a cost of medications. Differentiation between direct medical cost for the proposed methodology and current practice of the separate usage of insulin glargine 100 Ul/ml and lixisenatide was calculated. Discounting at 5% annually used in the calculation of the 3 years' time horizon. The results of health technology assessment are confirmed by sensitivity analysis. Microsoft Excel was used for calculation.Results. Calculation has been performed for two pens of Soliqua SoloStar® with different prices (Variation 1 and 2) in compare with different drugs of insulin glargine 100 Ul/ml and lixisenatide. Soliqua SoloStar® had less daily dose (by insulin glargine) on 22 UI vs free combination, and dose of lixisenatide was 20 mkg per day. Amount of patients who have reached HbA1c<7% was higher in Soliqua group vs free combination group on 29 % (95 % CI: 20,2-30,7; p<0,0001). Cost of daily dose in Variation 1 is 216,15 RUR., for Variation 2 - 172,48 RUR. In the same time cost of the free combination of insulin glargine 100 UI and lixisenatide is depended from trades name of the drug, while cost of lixisenatide per day is the same for free combination and has 158,8 RUR. Soliqua SoloStar® usage can decrease budget impact in comparison with free combination on 27,65-42,26 % (depending on cost of insulin glargine 100 UI from different manufacturers and Soliqua pen cost. Conclusion. Soliqua SoloStar® has pharmacoeconomics evidences to be included into the Governmental program of free medical Aid in Diabetes Mellitus type 2 patients.